Variable-angle locking plate with or without double-tiered subchondral support procedure in the treatment of intra-articular distal radius fracture - Kawasaki, Keikichi (J Orthop Traumatol, 2014)
BACKGROUND: Double-tiered subchondral support (DSS) procedure is two-row fixation in which proximal screws support the dorsal subchondral bone, whereas distal screws support the volar central subchondral bone, using the volar variable-angle locking plate to achieve better anatomical reduction. We examined whether DSS improves clinical outcome, complication rate, and loss of correction for dorsally displaced Arbeitsgemeinschaft für Osteosynthesefragen (AO) type C3 distal radius fractures. MATERIALS AND METHODS: We reviewed dorsally displaced intra-articular AO C3-type distal radius fractures treated at our institutions with a variable-angle volar locking plate. We assessed 49 patients (27 DSS; 22 non-DSS) treated with volar locking plates, with a mean age of 59.9 years and average follow-up of 20.2 months (range 12–56 months). We evaluated differences in functional outcome, complication rates, and loss of correction between groups using radiographic parameters. RESULT: There were no differences in clinical outcome and complications. Final volar tilt and ulnar variance were better maintained in the DSS group (P = 0.01 and 0.03). Change in volar tilt of the non-DSS group was more than that of the DSS group (P = 0.00). CONCLUSION: Though there were no significant differences in clinical outcomes, we identified a significant reduction in final volar tilt, ulnar variance, and change in volar tilt. DSS procedure is useful to avoid correction loss when treating unstable C3 distal radius fractures and thus would reduce posttraumatic arthrosis. LEVEL OF EVIDENCE: Level IV.